Marketing authorisation and pricing of FDA-approved cancer drugs in Brazil: a retrospective analysisResearch in context - Adriana M. Ivama-Brummell; Fernanda L. Marciniuk; Anita K. Wagner; Claudia G.S. Osorio-; Sabine Vogler; Elias Mossialos; Carla L. Tavares-; Huseyin Naci (Elsevier, 2023)
Summary: Background: Most cancer drugs enter the US market first. US Food and Drug Administration (FDA) approvals of new cancer drugs may influence regulatory decisions in other settings. The study examined whether characteristics of available evidence at FDA approval influenced time-to-marketing authorisation (MA) in Brazil, and price differences between the two countries. Methods: All new FDA-approved cancer drugs from 2010 to 2019 were matched to drugs with MA and prices approved in Brazil by December 2020. Characteristics of main studies, availability of randomised controlled trials (RCTs), overall survival (OS) benefit, added therapeutic benefit, and prices were compared. Findings: Fifty-six FDA-approved cancer drugs with matching indications received a MA at the Brazilian Health Regulatory Agency (Anvisa) after a median of 522 days following US approval (IQR: 351-932). Earlier authorisation in Brazil was associated with availability of RCT (median: 506 vs 760 days, p = 0.031) and evidence of OS benefit (390 vs 543 days, p = 0.019) at FDA approval. At Brazilian marketing authorisation, a greater proportion of cancer drugs had main RCTs (75% vs 60.7%) and OS benefit (42.9% vs 21.4%) than that in the US. Twenty-eight (50%) drugs did not demonstrate added therapeutic benefit over drugs for the same indication in Brazil. Median approved prices of new cancer drugs were 12.9% lower in Brazil compared to the US (adjusted by Purchasing Power Parity). However, for drugs with added therapeutic benefit median prices were 5.9% higher in Brazil compared to the US, while 17.9% lower for those without added benefit. Interpretation: High-quality clinical evidence accelerated the availability of cancer medicines in Brazil. The combination of marketing and pricing authorisation in Brazil may favour the approval of cancer drugs with better supporting evidence, and more meaningful clinical benefit albeit with variable degree of success in achieving lower prices compared to the US. Funding: None.